A review on propeller noise reduction techniques - Lim, Wei Cheng (Nanyang Technological University, 2021)
The objective of this report aims to review the current available methods in propeller noise reduction techniques. As more functions and technologies invented, many incorporate these capabilities into drones, creating miniature commercial and recreational purposes drones. Popularity of drones for such purposes began to grow rapidly and noise from drones become noticeable, causing a restriction in drone applications for daily usage. Prolonged exposure to the noise generated adverse effects on psychologically and physically. The report briefs on literature review, introducing the various types of noises produced by drones. Contributing to far-field noise, tip vortices were identified as the highest contributor to noise generation. This is mainly due to the pressure fluctuation, and vortices interacting with following blade. Turbulence flow encountered by airfoil also contribute to high level of far-field noise when kinetic energy produced within turbulence boundary layers scatter as it moves towards the trailing edge into wake. The report also includes several failure cases of studies produced previously. The various possible methods on noise reduction were evaluated and compared. This includes serrated trailing edge method which modify the trailing edge of the propeller to reduce noise, modification of blade tip with various design of tips proving the improvement and theory behind noise reduction, asymmetrical blade-spacing by moving blades into position affecting frequency distribution of propeller noise, implementation of leading edge boundary layer trips to remove laminar separation bubbles that amplifies the noise produced by blades and modification of airfoil along with diameter of propeller to enhance performance while performing in lower rpm with reduced tip speed. The report will go into selection of the effective methods to be implemented and tested via recommended experimental setup and drone. Fabrication of new blades shall aid in implementation of the methods, with the concept design of blades aim to combine several possible methods together to produce greater effects in noise reduction.